2019
DOI: 10.3389/fneur.2019.00749
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis of Hearing Loss in Patients Under Methadone Maintenance Treatment

Abstract: Background and Objective: Methadone maintenance treatment (MMT) as the most effective treatment for opioid addictions could induce both reversible and permanent hearing loss. Therefore, early detection of methadone-induced hearing loss is necessary to prevent irreversible cochlear damage. The present study aims to identify the early onset of hearing loss in patients who underwent MMT and to compare them with the age and gender matched normal hearing peers. Methods: This was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 26 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Vestibular function was not addressed. Bayat et al [2019] reported permanent bilateral HL in a group of 11 of 27 men in a treatment program undergoing methadone maintenance. HL onset (sudden vs. progressive), degree, and vestibular function were not reported.…”
Section: Prescription Opioidsmentioning
confidence: 98%
See 3 more Smart Citations
“…Vestibular function was not addressed. Bayat et al [2019] reported permanent bilateral HL in a group of 11 of 27 men in a treatment program undergoing methadone maintenance. HL onset (sudden vs. progressive), degree, and vestibular function were not reported.…”
Section: Prescription Opioidsmentioning
confidence: 98%
“…One additional study [Józefowicz-Korczynska et al, 1994] reported vestibular and audiometric results for people addicted to "drugs" that were not specified beyond noting inclusion of opiates, barbiturates, and inhalants. The remaining 27 studies (61%) reported ototoxicity from prescription of opioids including morphine, oxymorphone, hydrocodone, oxycodone [Kurnatowski and Garganisz, 1996;Ho et al, 2007;Rawool and Dluhy, 2011;Kopec and Nelson, 2012;Boyle and Rosenbaum, 2013;Helander et al, 2014;MacDonald et al, 2015;Leache et al, 2016;Ntranos et al, 2017;Mozeika et al, 2020], the combination of an opioid (hydrocodone, codeine, oxycodone, or dextropropoxyphene) and acetaminophen [Ramsay, 1991;Friedman et al, 2000;Oh et al, 2000;Blakley and Schilling, 2008;Rigby and Parnes, 2008;Freeman et al, 2009;Novac et al, 2015], and maintenance medications that included methadone or propoxyphene [Lupin and Harley, 1976;Harell et al, 1978;van Gaalen et al, 2009;Christenson and Marjala, 2010;Shaw et al, 2011;Vora-subin et al, 2013;Bayat et al, 2019;Ghasemi et al, 2019;Repple et al, 2021].…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Audiological tests were executed to categorize HL as mild (20-40 dB HL), moderate (41-70 dB HL), severe (71-95 dB HL), or profound (>95 dB HL) (Shinagawa et al, 2020). These assessments were executed in a standard anechoic chamber with a pure-tone audiometer at frequencies ranging from 250 to 4000 Hz (Bayat et al, 2019). Imaging investigations, for example, computed tomography (CT) scans and magnetic resonance imaging (MRI), did not reveal any abnormalities in anatomical structures of middle and inner parts of the ear in each patient.…”
Section: Clinical Presentationmentioning
confidence: 99%